Developing Faculty to Provide University Students With Improved Learning Experiences - Águeda Benito; Neal A. Green; Deborah R. Popely; Phuong M. Thai-Garcia; Art T. Schneiderheinze (Laureate Education Inc, 2017)
The article addresses the importance of incorporating faculty development as a key priority of higher education institutions. A literature review and some face-to-face and online interviews were conducted at various U.S. institutions, to identify common and best practices regarding this important matter. The article offers some ideas about what is done, and how it is done, to help faculty be ready for the challenging role they need to play: to be effective developers of a diverse student body that meets the evolving needs of industry and that utilizes technological tools that never existed before.